2012
DOI: 10.4317/medoral.17344
|View full text |Cite
|
Sign up to set email alerts
|

TWIST and p-Akt immunoexpression in normal oral epithelium, oral dysplasia and in oral squamous cell carcinoma

Abstract: Objectives: The aim of this study was to evaluate the immunoexpression of TWIST and p-Akt proteins in oral leukoplakia (OL) and oral squamous cell carcinoma (OSCC), correlating their expressions with the histological features of the lesions. Study design: Immunohistochemical studies were carried out on 10 normal oral epithelium, 30 OL and 20 OSCC formalin-fixed, paraffin-embedded tissue samples. Immunoperoxidase reactions for TWIST and p-Akt proteins were applied on the specimens and the positivity of the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 26 publications
1
29
0
3
Order By: Relevance
“…Although the mechanisms and the significance of this compartmentalization are largely unknown, previous investigations have shown variable distribution of p-Akt in different cellular compartments of oral premalignant and malignant lesions indicating that p-Akt localization may be related to differences in activity [10, 11]. In addition, differential subcellular (nuclear vs. cytoplasmic) p-Akt localization has been reported in other types of cancer and, as suggested, may play a significant role in determining its function [1215].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the mechanisms and the significance of this compartmentalization are largely unknown, previous investigations have shown variable distribution of p-Akt in different cellular compartments of oral premalignant and malignant lesions indicating that p-Akt localization may be related to differences in activity [10, 11]. In addition, differential subcellular (nuclear vs. cytoplasmic) p-Akt localization has been reported in other types of cancer and, as suggested, may play a significant role in determining its function [1215].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the localization of immunostaining, Pontes et al [10] reported that p-Akt was expressed mainly in both cytoplasmic and nuclear compartments, although restricted staining in either the nucleus or the cytoplasm was also occasionally observed. de Freitas Silva et al [11] also evaluated p-Akt immunohistochemical levels in oral lesions and reported a significant increase in OL and OSCC compared to NM; no significant differences among OL cases with different degrees of dysplasia were noted. With regard to localization, de Freitas Silva et al [11] reported that NM and OL cases showed p-Akt immunoreactivity limited to the nucleus, whereas OSCC cells expressed both nuclear and cytoplasmic immunostaining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vichalkovski et al have reported that activation of AKT upregulated the expression of Twist, subsequently decreasing chemotherapy-induced DNA damage, and inhibiting apoptosis [21]. Moreover, phosphorylated AKT is positively correlated with the high level of Twist as well as low expression of Ecadherin in oral squamous cell carcinoma [22]. In addition, the treatment of AKT inhibitor decreased the expression of Snail and Twist [23, 24] and eventually promoting the expression of Ecadherin, reducing the expression of Vimentin; restored the polygonal shape of cells, and stimulated the mesenchymal-epithelial transition (MET).…”
Section: Introductionmentioning
confidence: 99%
“…That is, intranuclear accumulation of p-AKT and nuclear exclusion of p27 to the cytoplasm was directly associated with the invasiveness of thyroid cancer cells with acquisition of mesenchymal phenotype, thereby suggesting AKT activation is involved in direct induction of EMT. Furthermore, this has been suggested by many others where levels of Snail and Twist and AKT phosphorylation were also positively correlated in oral squamous cell carcinoma and prostate carcinoma [2527]. In head and neck squamous cell carcinoma, PI3K/AKT activation degrades E-cadherin and promotes cell invasion and migration [28, 29].…”
Section: Discussionmentioning
confidence: 65%